[6]‐Shogaol, a Novel Chemopreventor in 7, 12‐Dimethylbenz[a]anthracene‐induced Hamster Buccal Pouch Carcinogenesis. (3rd February 2016) - Kathiresan, Suresh; Govindhan, Annamalai
Abstract : Oral cancer is a major cause of morbidity and mortality in developing countries. Despite advances in chemotherapy for the cancer management, the survival rate has not yet been improved. Dietary nutrient has been receiving a lot of attention and interest in the chemotherapeutic development. [6]‐Shogaol is a major bioactive compound identified in ginger that possesses many pharmacological properties. The aim of the present study is to investigate the effect of [6]‐shogaol on 7, 12‐dimethylbenz[a]anthracene‐induced hamster buccal pouch (HBP) carcinogenesis. Oral squamous cell carcinoma induced in HBP by painting with 0.5% 7, 12‐dimethylbenz(a)anthracene (DMBA), thrice in a week for 16 weeks. We observed 100% tumour incidence, decreased levels of lipid peroxidation, antioxidant, and phase II detoxification enzymes (GST, GR and GSH) in DMBA‐induced hamsters. Further, enhanced activity of phase I enzymes (cytochrome p450 and b5) and over‐expression of mutant p53, Bcl‐2 and decreased expression of wild type p53 and Bax were noticed in DMBA‐induced hamsters. Our results indicated that [6]‐shogaol (10, 20 and 40 mg/kg body weight) treated with DMBA‐painted hamsters, considerably reversed tumour incidence, improved antioxidant status, phase II detoxification enzymes, and also inhibit lipid peroxidation and phase I enzymes. Moreover, [6]‐shogaol inhibits mutant p53 and Bcl‐2 expression and significantly restored normal p53, Bax levels. Thus, we concluded that [6]‐shogaol prevents DMBA‐induced HBP carcinogenesis through its antioxidant as well as modulating apoptotic signals. Copyright © 2016 John Wiley & Sons, Ltd.